Herpes Simplex Virus 1 Protein UL37 Interacts with Viral Glycoprotein gK and Membrane Protein UL20 and Functions in Cytoplasmic Virion Envelopment - Jambunathan, Nithya (American Society for Microbiology, 2014)
We have shown that glycoprotein K (gK) and its interacting partner, the UL20 protein, play crucial roles in virion envelopment. Specifically, virions lacking either gK or UL20 fail to acquire an envelope, thus causing accumulation of capsids in the cytoplasm of infected cells. The herpes simplex virus 1 (HSV-1) UL37 protein has also been implicated in cytoplasmic virion envelopment. To further investigate the role of UL37 in virion envelopment, the recombinant virus DC480 was constructed by insertion of a 12-amino-acid protein C (protC) epitope tag within the UL37 amino acid sequence immediately after amino acid 480. The DC480 mutant virus expressed full-size UL37 as detected by the anti-protC antibody in Western immunoblots, accumulated unenveloped capsids in the cytoplasm of infected cells, and produced very small plaques on African green monkey kidney (Vero) cells that were similar in size to those produced by the UL20-null and UL37-null viruses. The DC480 virus replicated nearly 4 log less efficiently than the parental wild-type virus when grown on Vero cells. However, DC480 mutant virus titers increased nearly 20-fold when the virus was grown on FRT cells engineered to express the UL20 gene in comparison to the titers on Vero cells, while the UL37-null virus replicated approximately 20-fold less efficiently than the DC480 virus on FRT cells. Coimmunoprecipitation experiments and proximity ligation assays showed that gK and UL20 interact with the UL37 protein in infected cells. Collectively, these results indicate that UL37 interacts with the gK-UL20 protein complex to facilitate cytoplasmic virion envelopment. IMPORTANCE Herpes simplex viruses acquire their final envelopes by budding into cytoplasmic membranes derived from the trans-Golgi network (TGN). The tegument proteins UL36 and UL37 are known to be transported to the TGN sites of virus envelopment and to function in virion envelopment, since mutants lacking UL37 accumulate capsids in the cytoplasm that are unable to bud into TGN membranes. Viral glycoprotein K (gK) also functions in cytoplasmic envelopment, in a protein complex with the membrane-associated protein UL20 (UL20mp). This work shows for the first time that the UL37 protein functionally interacts with gK and UL20 to facilitate cytoplasmic virion envelopment. This work may lead to the design of specific drugs that can interrupt UL37 interactions with the gK-UL20 protein complex, providing new ways to combat herpesviral infections.